The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s1415-47572006000400004
|View full text |Cite
|
Sign up to set email alerts
|

Y-STR diversity and ethnic admixture in White and Mulatto Brazilian population samples

Abstract: We investigated 50 Mulatto and 120 White Brazilians for the Y-chromosome short tandem repeat (Y-STR) markers (DYS19, DYS390, DYS391, DYS392 and DYS393) and found 79 different haplotypes in the White and 35 in the Mulatto sample. Admixture estimates based on allele frequencies showed that the admixture of the white sample was 89% European, 6% African and 5% Amerindian while the Mulatto sample was 93% European and 7% African. Results were consistent with historical records of the directional mating between Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
(17 reference statements)
1
1
0
Order By: Relevance
“…Regarding skin colour, other studies demonstrated that Pro allele occurs at a high frequency in black (>60%) and the Arg allele in white-coloured (>70%) individuals (Själander et al 1996;Sucheston et al 2011). Our results could then be related to the ethnic admixture described in Brazilian population (Ferreira et al 2006). Although we have observed no association between TP53 codon 72 polymorfism and hair or eye colour, to the best our knowledge this is the first time reported for a Brazilian population sample.…”
Section: Discussionsupporting
confidence: 57%
“…Regarding skin colour, other studies demonstrated that Pro allele occurs at a high frequency in black (>60%) and the Arg allele in white-coloured (>70%) individuals (Själander et al 1996;Sucheston et al 2011). Our results could then be related to the ethnic admixture described in Brazilian population (Ferreira et al 2006). Although we have observed no association between TP53 codon 72 polymorfism and hair or eye colour, to the best our knowledge this is the first time reported for a Brazilian population sample.…”
Section: Discussionsupporting
confidence: 57%
“…This value is higher than those found in other studies from the Brazilian population, based on five and eight Y-STR core markers. 11,18 Gene diversity values of these 16 Y-STR ranged from 0.5262 (DYS393) 7 to 0.8962 (DYS385). 7 The Neighbor-Joining Tree constructed from the FST values shows that Santa Catarina and Portuguese populations are in the same cluster.…”
Section: Other Remarksmentioning
confidence: 99%